Oil Price Risk Exposure at Industry and Subsector Levels: A Case Study - Shaeri, Komeil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
[Abstract Not Available]
Doctor of Philosophy in Banking and Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2016. Co-Supervisor: Prof. Dr. Cahit Adaoğlu andf Supervisor: Prof. Dr. Salih Katırcıoğlu
Keywords: Banking and Finance; Petroleum--resource economics; Energy industries--Oil Proces--Risk management; Oil price risk exposure; Equity returns; multiple structural breaks; Fama-French five-factor model; time-varying causality; cointegration